Covalent bonds against magnetism in transition metal compounds - Streltsov, Sergey V. (Proc Natl Acad Sci U S A, 2016)
Magnetism in transition metal compounds is usually considered starting from a description of isolated ions, as exact as possible, and treating their (exchange) interaction at a later stage. We show that this standard approach may break down in many cases, especially in 4d and 5d compounds. We argue that there is an important intersite effect—an orbital-selective formation of covalent metal–metal bonds that leads to an “exclusion” of corresponding electrons from the magnetic subsystem, and thus strongly affects magnetic properties of the system. This effect is especially prominent for noninteger electron number, when it results in suppression of the famous double exchange, the main mechanism of ferromagnetism in transition metal compounds. We study this mechanism analytically and numerically and show that it explains magnetic properties of not only several 4d–5d materials, including Nb(2)O(2)F(3) and Ba(5)AlIr(2)O(11), but can also be operative in 3d transition metal oxides, e.g., in CrO(2) under pressure. We also discuss the role of spin–orbit coupling on the competition between covalency and magnetism. Our results demonstrate that strong intersite coupling may invalidate the standard single-site starting point for considering magnetism, and can lead to a qualitatively new behavior.